Insights into the effects of biomass feedstock and pyrolysis conditions on the energy storage capacity and durability of standard biochar-based phase-change composites - Dimberu G. Atinafu; Ji Yong Choi; Jihee Nam; Yujin Kang; Sumin Kim (Biochar)
Abstract Material selection and production conditions are imperative for determining the functional performances of composite materials. Phase-change composites obtained from phase-change materials (PCMs) and supporting matrices exhibit high thermal energy storage density. They are used to overcome the intermittency issues of wind and solar energy, as well as to reduce waste heat dissipation to the environment. However, the large-scale utilization of composite and pristine materials has severe drawbacks, primarily stemming from the complex fabrication routes of the encapsulating agents, leakage, and inadequate thermal stability. In this study, biochar-based phase-change composites were fabricated using vacuum infiltration techniques, and the effects of biomass feedstock and pyrolysis temperature on the performance of the composite were elucidated using different types of biowastes and temperatures. This approach has several advantages, including facile production techniques, low-cost carbon sources, and environmental friendliness. The PCM adsorption ratio of biochars derived from rice husk (RH) and Miscanthus straw linearly correlated with the pyrolysis temperature (550–700 °C), while RH700 resulted in a composite with a high enthalpy per unit mass of hexadecane (HXD) in RH700/HXD (250.9 J g−1) owing to the high surface area of RH700 (74.66 m2 g−1). The crystalline temperature increased slightly from 10.7 °C in RH550/HXD to 10.9 °C in RH700/HXD, suggesting improved molecular motion and crystal growth of HXD. Wheat straw biomass pyrolyzed at a low temperature (550 °C), displaying a reduced surface area at 700 °C (7.35 m2 g−1) and exhibiting the lowest energy storage density. The latent heat efficiency reached 99.5–100%, where RH700/HXD exhibited 100% efficiency. The composites demonstrated strong leakage resistance at high heating temperatures (60 °C, above the melting temperature of HXD), good chemical compatibility between the biochar and HXD, and high durability after 500 thermal cycles. Therefore, the extent of PCM loading and energy storage density improvements primarily depends on the pyrolysis conditions, feedstock used, and pore size distribution of the biochar samples. This research provides insights into the fabrication of phase-change composites and optimization of the carbonization process of different biomasses used for thermal management applications, such as building energy savings. Graphical Abstract